Mechanistic understanding of the corrosion behavior of Mg4Zn0.2Sn alloys: From the perspective view of microstructure. (September 2020) - Jiang, Pingli; Blawert, Carsten; Scharnagl, Nico; Bohlen, Jan; Zheludkevich, Mikhail L.
Highlights: Extrusion significantly improved the corrosion resistance of Mg4Zn0.2Sn alloy. Zinc alternately segregated between the α-Mg matrix in the extruded alloy. Micro-galvanic corrosion was revealed between Zinc-segregated areas and matrices in both conditions. The intensity of micro-galvanic coupling was reduced after extrusion. Abstract: The corrosion behavior of as-cast and extruded Mg4Zn0.2Sn ( wt. %) alloys was comprehensively compared in 0.5 wt. % NaCl solution. Microstructure and surface chemistry related corrosion performance has been revealed. Zinc-supersaturated solid solution is formed around the intermetallics in the as-cast alloy, but zinc alternately segregates between the α-Mg matrix in the extruded alloy. According to Scanning Kelvin Probe Force Microscopy and immersion tests, micro-galvanic corrosion between the precipitates (intermetallics or impurity particles) or Zinc-rich area and the matrix resulted in severe localized corrosion in both conditions. However, alternation of microstructure induced by extrusion significantly enhanced the corrosion resistance of Mg4Zn0.2Sn alloy.